2016
DOI: 10.1101/095794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Multi-instance Networks with Sparse Label Assignment for Whole Mammogram Classification

Abstract: Abstract. Mammogram classification is directly related to computer-aided diagnosis of breast cancer. Traditional methods requires great effort to annotate the training data by costly manual labeling and specialized computational models to detect these annotations during test. Inspired by the success of using deep convolutional features for natural image analysis and multi-instance learning for labeling a set of instances/patches, we propose end-to-end trained deep multiinstance networks for mass classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…For some types of data, especially images, it is straightforward to augment training datasets by splitting a single labelled example into multiple examples. For example, an image can easily be rotated, flipped or translated and retain its label [ 43 ]. 3D MRI and 4D fMRI (with time as a dimension) data can be decomposed into sets of 2D images [ 491 ].…”
Section: Discussionmentioning
confidence: 99%
“…For some types of data, especially images, it is straightforward to augment training datasets by splitting a single labelled example into multiple examples. For example, an image can easily be rotated, flipped or translated and retain its label [ 43 ]. 3D MRI and 4D fMRI (with time as a dimension) data can be decomposed into sets of 2D images [ 491 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small volume segmentation suffers from the imbalanced data problem, where the number of voxels inside the small region is much smaller than those outside, leading to the difficulty of training. New classes of loss functions have been proposed to address this issue, including Tversky loss, generalized Dice coefficients, focal loss, sparsity label assignment deep multi‐instance learning, and exponential logarithm loss . However, we found that none of these solutions alone was adequate to solve the extremely data imbalanced problem (1/100 000) we face in segmenting small OARs, such as optic nerves and chiasm, from HaN images.…”
Section: Introductionmentioning
confidence: 95%
“…The obtained results are reported in Tables 2 and 3. Table 3 results have been taken from paper [17] for DeepCAD, CNN-MAX-CAD-Qiu and CNN-CAD-Jiao and for Ball and Varela has been taken from [18]. Ball shows 87% accuracy on DDMS dataset, Varela shows 81% on DDMS dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Again there is no rule that which features are most suitable. Classification has been performed by using some old classifiers like artificial neural network, KNN, Bayesian [17], [18]. But most of the times, these features extraction and classifiers are not suitable.…”
Section: Introductionmentioning
confidence: 99%